Endothelial Cell Orientation and Polarity Are Controlled by Shear Stress and VEGF Through Distinct Signaling Pathways - Vion, Anne-Clémence; Perovic, Tijana; Petit, Charlie; Hollfinger, Irene; Bartels-Klein, Eireen; Frampton, Emmanuelle; Gordon, Emma; Claesson-Welsh, Lena; Gerhardt, Holger (Frontiers in Physiology, 2021)
Vascular networks form, remodel and mature under the influence of multiple signals of mechanical or chemical nature. How endothelial cells read and interpret these signals, and how they integrate information when they are exposed to both simultaneously is poorly understood. Here, we show using flow-induced shear stress and VEGF-A treatment on endothelial cells in vitro, that the response to the magnitude of a mechanical stimulus is influenced by the concentration of a chemical stimulus, and vice versa. By combining different flow levels and different VEGF-A concentrations, front-rear polarity of endothelial cells against the flow direction was established in a flow and VEGF-A dose-response while their alignment with the flow displayed a biphasic response depending on the VEGF-A dose (perpendicular at physiological dose, aligned at no or pathological dose of VEGF-A). The effect of pharmaceutical inhibitors demonstrated that while VEGFR2 is essential for both polarity and orientation establishment in response to flow with and without VEGF-A, different downstream effectors were engaged depending on the presence of VEGF-A. Thus, Src family inhibition (c-Src, Yes, Fyn together) impaired alignment and polarity without VEGF-A while FAK inhibition modified polarity and alignment only when endothelial cells were exposed to VEGF-A. Studying endothelial cells in the aortas of VEGFR2Y949F mutant mice and SRCiEC-KO mice confirmed the role of VEGFR2 and specified the role of c-SRC in vivo. Endothelial cells of VEGFR2Y949F mutant mice lost their polarity and alignment while endothelial cells from SRCiEC-KO mice only showed reduced polarity. We propose here that VEGFR2 is a sensor able to integrate chemical and mechanical information simultaneously and that the underlying pathways and mechanisms activated will depend on the co-stimulation. Flow alone shifts VEGFR2 signaling towards a Src family pathway activation and a junctional effect (both in vitro and in vivo) while flow and VEGF-A together shift VEGFR2 signaling towards focal adhesion activation (in vitro) both modifying cell responses that govern orientation and polarity.